Strategi Komunikasi Politik Fadjroel Rachman dalam Menyampaikan Kebijakan Pemerintah Kepada Publik Saat Pandemi Covid-19 - Nurul Aisyah Rahmawati; Muhammad Aryo Hakim; Rahastri Chaliza; Achmadrifai Achmadrifai; Mitha Aulia Usrul; Muhammad Faiz Mumtaz; Harmoni Harmoni (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This study aims to analyze the political communication strategies employed by Fadjroel Rachman as the Special Staff to the President for Communication in disseminating government policies during the COVID-19 pandemic. Using a descriptive qualitative approach through library research, this study explores various documents, academic articles, online news, and official government sources. The findings reveal that Fadjroel implemented adaptive and collaborative communication strategies by using war metaphors as symbolic crisis communication and by applying transparent and dialogical approaches in public messaging. Furthermore, the integration of social media and conventional media, along with collaboration with community leaders, strengthened the dissemination of information and increased the legitimacy of government policies. These findings suggest that responsive and empathetic political communication plays a crucial role in public crisis management. This research provides practical implications for policymakers in communication strategy and offers potential for further exploration in the field of political communication during crises.